A new measurement of direct CP violation in two pion decays of the neutral kaon - Fanti, V; Lai, A; Marras, D; Musa, L; Bevan, A; Gershon, T; Hay, B; Moore, R; Moore, K; Munday, D; Needham, MD; Parker, M; et al. (1999)
The NA48 experiment at CERN has performed a new measurement of direct CP violation, based on data taken in 1997 by simultaneously collecting KL and KS decays into π0π0and π+π-. The result for the CP violating parameter Re(ε′/ε′) is (18.5 ± 4.5(stat) ± 5.8(syst)) × 10-4. © 1999 Elsevier Science B.V. All rights reserved.